Infectivity in full-term placenta of Zika viruses with different lipid profiles - Eva Mazzetto; Alessio Bortolami; Davide Bovo; Matteo Stocchero; Elisa Mazzacan; Alessandra Napolitan; Valentina Panzarin; Maria Rosa Tran; Gianpiero Zamperin; Adelaide Milani; Andrea Fortin; Michela Bigolaro; et al. (Virus Research)
Among flaviviruses, Zika virus (ZIKV) is the only arbovirus officially recognized as a teratogenic agent, as a consequence of its ability to infect and cross the placental barrier causing congenital malformation in the fetus. While many studies have focused on understanding ZIKV pathogenesis during pregnancy, the viral mechanisms affecting fetal development remain largely unclear. In this study, we investigated ZIKV virulence in placental trophoblasts, using viruses with distinct lipid profiles. Firstly, we propagated a ZIKV strain belonging to the Asian lineage in either mammalian or mosquito cells, obtaining two viral stocks, which were purified and analyzed to determine their genetic and lipid composition. Successively, we assessed the infectivity of the two stocks in placental cells using both immortalized cell lines and explants. We found that the two viral stocks displayed identical consensus sequences with homogeneous quasispecies composition. However, the lipid composition of their envelope significantly varied depending on the cell of origin, with the mammalian-derived viral stock characterized by a higher content of phosphatidylcholines compared to the virions originating from mosquito cells. Notably, ZIKV stock derived from mammalian cells showed a higher infectivity in immortalized villous trophoblasts and full-term placental explants of human origin. This increased infectivity was linked to enhanced fusion efficiency during the viral uncoating phase in trophoblast cells, as demonstrated using a lipophilic probe. Collectively, our data suggest a potential role of viral lipids as determinants of ZIKV infectivity in full-term placenta, underscoring the importance of lipidomic research in virology.